Body mapping chart for estimation of percentage of body surface area in mesocephalic dogs. Issue 3 (24th December 2021) - Henriksson, Andrea; Kuo, Kendon; Gerken, Katherine; Cline, Kelsey; Hespel, Adrien‐Maxence; Cole, Robert; Moon, Rachel
Abstract: Objective: To create a chart for estimating body surface area (BSA) for use in canine burn victims, similar to the human Rule of Nines. Design: Prospective study, from 2016 to 2017. Setting: University teaching hospital. Animals: Nine adult, medium‐sized, mesocephalic dogs (5 females, 4 males). Interventions: Sedated dogs and fresh cadavers underwent full‐body computed tomography (CT) scans. A 3‐dimensional technique was used to calculate the surface area of specific body parts, as well as the surface area of the whole body. With the obtained measurements, a BSA chart was created. Measurements and Main Results: Estimates for percent of total BSA obtained with CT images were as follows: head and abdomen 14%, respectively, neck and each of the thoracic limbs 9%, thorax 18%, pelvic limbs 11% each, and pelvis including the tail 5%. The most considerable differences between dogs and people in respect to the Rule of Nines chart were noticed in the head, the pelvic limbs, as well as in the groin region in people as compared with the pelvic/tail area in dogs. The surface areas of the front legs and thorax were the only body parts that corresponded with that of human body surfaces. Conclusions: A chart for estimating canine body surface was created. Given the diversity of dog breeds, sizes, and body conformation, our results cannot be generalized to all dogs. Studies of more diverse populations are warranted.